To reconstruction of the river’s categories which formed sedimentary basins of Riphean basins in the region of the Eastern European platform and modern south Urals juncture - A. V. Maslov (Известия высших учебных заведений: Геология и разведка)
Information on the distribution of trace and rare-earth elements in the bottom sediments of estuarine zones of various river categories (large rivers, rivers draining water collections, composed of sedimentary or magmatic and metamorphic rocks, etc.) of silt and pelitic dimensions can be considered as the data, reflecting characteristic features of the suspention, transported to marine basins from various catchment provinces. In certain situations, the composition of the surface bottom sediments of the marine basin is determined by the suspension composition of any large river flowing into it (the Caspian Sea and the Volga River, the Laptev Sea and the Lena River, etc.). The similarity and difference in the rare-earth elements (REE) systematics of bottom sediments of estuarine zones and suspended particulate matter of rivers of various categories is quite well expressed in the pair diagrams (La/ Yb)N–(Eu/Sm)N, (La/Yb)N–Th, etc. A comparison of the features of the distribution of REE and Th in the Riphean clay rocks of the Southern Urals and in bottom sediments of the estuaries of various categories of recent rivers has been performed. It has been concluded that clay rocks forming a typical Riphean section are formed due to the erosion of mainly or predominantly sedimentary and/or metasedimentary complexes that existed during the PreRiphean or the Riphean in the east part of the East European platform and have not survived to date.